Two new species of Impatiens (Balsaminaceae) from Gaoligong Mountains, Yunnan, China - Hu, Tian; Peng, Shuai; Zhou, Xin-Xin; Zheng, Yi-Ming; Cong, Yi-Yan; Hu, Guang-Wan (Phytotaxa, 2022)
Impatiens longyangensis and I. yaojiapingensis, two new species from Gaoligong Mountains, Yunnan, China, are described here. The former species is morphologically similar to I. shangjiangensis, but differs by its shorter petioles and peduncle, ovate bract, shortly saccate lower sepal with a longer spur and suborbicular dorsal petal. The latter is similar to I. sterilis, and differs by its pubescent leaf, petiole with one to three pairs of clavate glands, persistent bract, lower sepal with a straight spur and suborbicular dorsal petal. Molecular phylogenetic analysis based on nuclear ITS and plastid atpB-rbcL sequences shows that the two new species belong to I. sect. Racemosae.